Imaging reservoir quality of Knurr and Stø Formations in the Hammerfest Basin and Ringvassøy-Loppa Fault Complex, Norwegian Barents Sea - Zhang, Dechen (2014)
The Barents Sea is a prospective area in terms of hydrocarbon resources with high ratio of discovery wells. This study focuses on reservoir quality of two sandstone reservoirs of Knurr and Stø Formations in the Hammerfest Basin and Ringvassøy-Loppa Fault Complex in the Norwegian Barents Sea. The study methods include petrophysics analysis, rock physics diagnostics and AVO modelling. Seven exploration wells from the study area are analysed to investigate the reservoir quality of two target reservoirs. The studied reservoir sandstones are buried at different depth levels from approximately 1400 m to 3300 m (RKB). Therefore, this database provides a perfect profile for sandstone compaction and diagenetic studies. A comparison of Vp-depth trends in studied wells and published Vp-depth trends for normally subsided basins shows that the Vp in the study area are much higher than expected. The calculated average porosity values of the reservoirs are much lower than published porosity-depth trends. Regional uplift and erosion is attributed as the main reason for these anomalous values. The estimated average uplift in the study area is about 900 m. The exhumation decrease to the north-west direction. After estimation of uplift, the present depth is corrected to a maximum burial depth. New depth data are subsequently used to calculate maximum burial temperatures for the reservoirs. The maximum temperatures show that the sediments have experienced much higher thermal exposures than what is interpolated from bottom hole temperatures. All the reservoirs in the studied wells are within the zone of chemical compaction. It is clear from petrophysical analysis that the reservoir quality of the Knurr Formation is poorer compared to the Stø Formation. The Knurr Formation is deposited in a submarine fan system while the Stø Formation is deposited in a coastal environment. Different sedimentary environments result in different reservoir parameters, like net-to-gross ratio, shale volume and porosity. Rock physics templates work well for estimating quartz cement content and for distinguishing different lithologies and pore fluids. Even the shallowest buried sandstones (around 1200 meters below sea floor) in well 7119/12-2 contain cements between the grains according to rock physics diagnostic results. This is also confirmed by published literatures. Secondary porosity is also common in the studied wells. A clear trend of rock properties with increasing depth is observed in all of the rock physics templates used. Lamda-Rho versus Mu-Rho cross plot works better than Vp/Vs versus IP cross plot for discriminating the lithology and fluid in the studied wells. Due to the complex compaction and diagenetic history, the shear wave velocity measured in well 7119/12-4 is abnormally high. These high shear wave velocities result false gas effect in rock physics templates (e.g. Vp/Vs versus IP and LMR). The AVO modelling results agree reasonably well with the classical AVO theory. The gas-bearing data points deviate from the background trend at both the top and bottom interfaces of the reservoirs. An impedance inversion with increasing depth is observed in the AVO modelling for the Stø Formation sandstones. With increasing depth, the soft sandstones turn into hard sandstones compared to the overlying shale. The AVO modelling results are sensitive to many factors, like water saturation, wavelet and block size. The measured Vs values in well 7119/12-4 also result false gas effect in AVO modelling.